2005
DOI: 10.1017/s0022029905000725
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the thermal inactivation of the Lactococcus lactis bacteriophage P008

Abstract: The thermal resistance of the lactococcal bacteriophage P008 was investigated between 55 and 80 degrees C. Inactivation kinetics revealed an order of reaction above 1 and could be determined by a non-1st-order regression model. Phage inactivation was influenced by the medium (milk and Ca-M17-broth). Within the investigated temperature range, milk had a protective effect on phage P008. This was reflected in the rate constant and in the activation energy. Thermal phage inactivation studies reported in literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 12 publications
2
29
0
3
Order By: Relevance
“…38 Dairy phages in milk show significantly higher survival under thermal stress when compared with phages suspended in water. 39 The protective effect is not due to the fat component of milk because it is also seen in reconstituted nonfat dry skim milk. 40 As casein is the main protein in cow milk, it was also considered as an excipient that may have the potential to provide protection against processing loss.…”
Section: Excipientsmentioning
confidence: 99%
“…38 Dairy phages in milk show significantly higher survival under thermal stress when compared with phages suspended in water. 39 The protective effect is not due to the fat component of milk because it is also seen in reconstituted nonfat dry skim milk. 40 As casein is the main protein in cow milk, it was also considered as an excipient that may have the potential to provide protection against processing loss.…”
Section: Excipientsmentioning
confidence: 99%
“…Protective effects, in which the food matrix protects microorganisms from physicochemical treatments (e.g., by preventing them from being inactivated), are well known for bacteria (45,48) and have been described for some bacteriophages (67,73). In this study, the food-specific protective effects were investigated by comparing treated food samples with treated reference samples, in which the food was replaced by PBS.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study on phage dissemination in whey powders, it was shown that 94% of the samples contained lytic phages up to titres of 10 7 pfu g À1 (Wagner, 2012). In previous studies, heat inactivation has been studied in detail, and it was documented that most phages can withstand pasteurization processes of 72e75 C for 15e30 s (Atamer et al, 2009;Atamer & Hinrichs, 2010;Müller-Merbach, Neve, & Hinrichs, 2005;Quiberoni, Guglielmotti, & Reinheimer, 2003;Su arez & Reinheimer, 2002). Consequently, thermo-resistant phages are capable of propagating during cheese processing, resulting in phage titres up to 10 9 phages per mL in drained cheese whey (Neve, 1996;Neve, Berger, & Heller, 1995).…”
Section: Introductionmentioning
confidence: 95%